Correlation and diagnostic significance of CD4 T cell subsets and NLRP3 inflammasome in ulcerative colitis: the role of the NLRP3/T-bet/GATA3 axis - Yingnan Hu; Jingyi Tang; Dian Yu; Shuo Su; Jintao Fang; Linying Xia; Wenjun Xu; Weihan Zhu; Ninping Song; Fengyong Wang; Dechang Diao; Wei Zhang (BMC Gastroenterology)
Abstract Background and aim Ulcerative colitis (UC) is characterized by complex immunological interactions involving CD4 T cell subsets and the NLRP3 inflammasome, which influence inflammatory responses. This investigation focused on delineating the activation profiles of these components and their correlation with disease severity and activity, assessing their diagnostic implications in UC. Methods We conducted immunohistochemistry and ELISA assays to measure markers expression of CD4 T cell subsets and the NLRP3 inflammasome in UC patients versus controls. Findings were validated using correlation analysis, molecular docking and ROC curves. Results UC patients displayed increased Th1 (T-bet, TNF-α), Th2 (GATA3, IL-6), and Th17 (RORγt, IL-17, IL-22, IL-23) markers versus controls. Additionally, Th1 and Th2 cytokines (IL-2 and IL-4) were significantly elevated in severe UC, while Treg markers (FOXP3, IL-10, TGF-β1) were elevated only in mild-to-moderate UC. Enhanced NLRP3 inflammasome activation, indicated by elevated NLRP3, Caspase-1, and IL-1β levels. These molecular patterns, confirmed through correlation analysis and molecular docking, underscored strong correlations among NLRP3, T-bet, and GATA3, supporting the proposed NLRP3/T-bet/GATA3 axis. This axis, along with other biomarkers, showed strong associations with UC severity, Mayo score, UCEIS, demonstrated relatively high diagnostic value. Conclusion The NLRP3/T-bet/GATA3 axis provides a referable strategy for multi-targeted combined treatment of UC and may serve as potential biomarkers for enhancing diagnostic accuracy and guiding therapy.